Investigating the Challenges of Medical tourism Development in Affiliated Centers of Iran University of Medical Sciences (IUMS) - fatemeh Najafipoor Moghadam; Nader Tavakoli; Hossein Farzaneh (Shahid Sadoughi University of Medical Sciences, 2023)
Background: This study was conducted with the aim of investigating the challenges of health tourism development in affiliated centers of Iran University of Medical Sciences (IUMS). Methods: This was a qualitative, descriptive, and applied study. The statistical population included all the stakeholders of health tourism at IUMS. The information was obtained through purposeful sampling until data saturation was reached. 20 experts in health tourism at the IUMS were interviewed. Experts confirmed the validity of form and content and coding was done (1),  and the final result was presented. Results: 4 general categories were identified as the challenges of health tourism development in IUMS. They included political, social and economic conditions (communication at the global level and economic development), structural and internal organizational conditions (bureaucratic and administrative, supervisory and communication processes), participation (bureaucratic processes, effective communication between government departments and drafting of strategies and operational plans), and promotion (developing a strategic and coherent plan in the development of marketing and services at the global level and advertising). Conclusion: While identifying the driving factors and obstacles, It is necessary to develop medical tourism, pay attention to the political, social and economic, structural and intra-organizational conditions, attract participation and improve the existing situation and design services, which are among the challenges of medical tourism development at the Iran University of Medical Sciences.